Implementation of treatment guidelines for specialist mental health care. - Barbui, C; Girlanda, F; Ay, E; Cipriani, A; Becker, T; Koesters, M (Oxford University Press, 2014)
Although treatment guidelines are commonly employed in healthcare settings, it remains unclear whether their use has any positive impact on the performance of mental health services or whether they improve patient outcomes. This systematic review is based on a search carried out in March 2012 and includes 5 randomized studies that examined the effectiveness of guideline implementation strategies in improving healthcare services and outcomes for people with mental illness. The 5 studies were generally at unclear risk of bias, and all evidence in the “Summary of Findings” table was graded by review authors as of very low quality. Although single studies provided initial evidence that implementation of treatment guidelines may achieve small changes in mental health practice, with only 5 studies meeting inclusion criteria, and with limited usable information, it is not possible to arrive at definitive conclusions. A gap in knowledge still exists about how guideline implementation strategies might improve patient outcomes and health services. This leaves scant information for people with mental health problems, health professionals, and policy makers. More large-scale, well-designed and well-conducted studies are necessary to fill this gap in knowledge.